State Regulation of Humanitarian Policy in the Context of Hybrid Warfare - Сащук, Ганна Миколаївна (Київський національний університет імені Тараса Шевченка, 2024)
The author analyzes the key state mechanisms for regulating humanitarian policy in modern conditions, the specifics of hybrid warfare in the humanitarian sphere, the gaps in Ukraine’s humanitarian policy that contributed to the success of the Russian hybrid war, and the gaps in the Russian humanitarian policy. It is revealed that the continued presence of the Russian mass product within the Ukrainian socio-cultural environment created opportunities for further broadcasting and perception of hybrid information attitudes and fakes of Russian propaganda. It is found that in the context of hybrid warfare, hybrid narratives are used to disseminate simplified, distorted and primitive ideas about the world, specific events, often embodied within mythologies, clear binary opposites and rational understanding of events, replacing reality with another, irrational and sensual picture. It is proved that modern hybrid wars encourage the international community to actively revise the main principles and methods of state regulation of humanitarian policy. Of particular importance is the need for revisions, modernization of the conceptual and theoretical foundations of state regulation of the humanitarian component of the country’s security, its role in strengthening sovereignty and national stability.

Проаналізовано ключові державні механізми регулювання гуманітарної політики в сучасних умовах, специфіка ведення гібридної війни у гуманітарній сфері, прогалини гуманітарної політики України, які сприяли успіху російської гібридної війни, а також. Виявлено, що тривала присутність російського масового продукту в межах українського соціокультурного середовища створювала можливості для подальшої трансляції та сприйняття гібридних інформаційних установок та фейків російської пропаганди. З’ясовано, в умовах гібридної війни використовуються гібридні наративи, покликані поширювати спрощені, спотворені та примітивні уявлення про світ, конкретні події, часто втілені в рамках міфологем, чіткі бінарні протилежності та раціональне розуміння подій, підміняючи реальність іншою, ірраціонально-чуттєвою картиною. Доведено, що сучасні гібридні війни спонукають світове співтовариство до активного перегляду головних принципів і методів державного регулювання гуманітарної політики. Ключового значення для безпеки країни у сучасних умовах набуває потреба оптимізації державного регулювання гуманітарної політики у контексті зміцненні суверенітету та національної стійкості.
Державне регулювання гуманітарної політики в умовах гібридної війни
Keywords: humanitarian sphere; humanitarian policy; humanitarian resilience; hybrid warfare; hybrid narratives; national security; гуманітарна сфера; гуманітарна політика; гуманітарна стійкість; гібридна війна; гібридні наративи; національна безпека